2019
DOI: 10.1159/000500621
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype Evolution and Distinct Evolutionary History of the W Chromosomes in Swallows (Aves, Passeriformes)

Abstract: As in many other bird groups, data on karyotype organization and distribution of repetitive sequences are also lacking in species belonging to the family Hirundinidae. Thus, in the present study, we analyzed the karyotypes of 3 swallow species (Progne tapera, Progne chalybea, and Pygochelidon cyanoleuca) by Giemsa and AgNOR staining, C-banding, and FISH with 11 microsatellite sequences. The diploid chromosome number was 2n = 76 in all 3 species, and NORs were observed in 2 chromosome pairs each. The microsatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Nevertheless, recent studies using classical and molecular cytogenetics have shown a greater similarity between the P. tapera and P. chalybea when compared to P. cyanoleuca (Barcellos et al, 2019). Taken together, these examples and our data support the current phylogeny of the genus Progne, which puts all Progne species into a single genus (Sheldon et al, 2005;Moyle et al, 2008;Barcellos et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Nevertheless, recent studies using classical and molecular cytogenetics have shown a greater similarity between the P. tapera and P. chalybea when compared to P. cyanoleuca (Barcellos et al, 2019). Taken together, these examples and our data support the current phylogeny of the genus Progne, which puts all Progne species into a single genus (Sheldon et al, 2005;Moyle et al, 2008;Barcellos et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…The diploid number is 76 for the three swallow species, which corroborate previous studies (Barcellos et al, 2019). The 1st, 4th, 10th pairs and also the Z chromosome are metacentric, pairs 2 and 3 are acrocentric, while 8th, 9th, 11th and all microchromosomes are telocentric.…”
Section: Karyotype Analysessupporting
confidence: 89%
See 3 more Smart Citations